Happiness functions with preference interdependence and heterogeneity: The case of altruism within the family - Adrian Bruhin; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2007)
This study investigates the prevalence and extent of altruism by examining the relationship between parents' and their adult children's subjective well-being in a data set extracted from the German Socio-Economic Panel. In order to segregate the share of parents with altruistic preferences from those who are selfish, we estimate a finite mixture regression model. We control for various sources of potential bias by taking advantage of the data's panel structure. To validate our modeling approach we show that predicted altruists indeed make higher average transfer payments.
Keywords: C23; D64; 330; altruism; subjective well-being; finite mixture regression models; Altruismus; Lebensqualität; Familie; Schätzung; Deutschland